ANALISIS USAHA RUMAH MAKAN SARI LAUT DI KECAMATAN TANJUNG REDEB KABUPATEN BERAU - Hendriyansyah; Nurul Ovia Oktawati; Dayang Diah Fidhiani (2339-1324, 2016)
The purpose of research were to analyzid benefit, revenue cost ratio (RCR) and breakeven point (BEP) of production and price of sea food restaurant in Tanjung Redeb Subdistrict Berau District. Sampling methods use census method. the result shows the sea food restaurant in Tanjung Redeb sub district is profitable with profil Rp. 4.713.070.500,- per respondent per year. With average Rp. 147.283.453,- per year. With the average RCR 1,22. Based on BEP analysis known the actual condition of sea food restaurant is above BEP production and price